Pharmacokinetic assessment of tacrolimus in combination with deoxyschizandrin in rats - Sun, Jianguo; Wang, Zhipeng; Liu, Na; Liu, Zhijun; Cui, Lili; Tao, Xia; Chen, Wansheng; Gao, Shouhong; Wu, Zhijun (Frontiers in Pharmacology, 2024)
Background: Tacrolimus (Tac) is commonly used for postoperative immunosuppressive therapy in transplant patients. However, problems, for example, low bioavailability and unstable plasma concentration, persist for a long time, Studies have reported that the deoxyschizandrin could effectively improve these problems, but the pharmacokinetic parameters (PKs) of Tac combined with deoxyschizandrin are still unknown. Method: In this study, an UHPLC-MS/MS method has been established for simultaneous quantitation of Tac and deoxyschizandrin. The PKs of Tac influenced by different doses of deoxyschizandrin after single and multiple administrations were analyzed, and the different impact of deoxyschizandrin and Wuzhi capsule on PKs of Tac were compared. Result: The modified UHPLC-MS/MS method could rapid quantification of Tac and deoxyschizandrin within 2 min using bifendatatum as the internal standard (IS). All items were successfully validated. The Cmax of deoxyschizandrin increased from 148.27±23.20 to 229.13±54.77 ng/mL in rats after multiple administrations for 12 d. After co-administration of 150 mg/mL deoxyschizandrin, Tac had an earlier Tmax and greater Cmax and AUC0–t, and the Cmax and AUC0–t of Tac increased from 14.26±4.73 to 54.48±14.37 ng/mL and from 95.10±32.61 to 315.23±92.22 h/ng/mL, respectively; this relationship was positively proportional to the dosage of deoxyschizandrin. In addition, compared with Wuzhi capsule, the same dose of deoxyschizandrin has a better effective on Tac along with more stable overall PKs. Conclusion: An UHPLC-MS/MS method was established and validated for simultaneous detection of deoxyschizandrin and Tac. Deoxyschizandrin could improve the in vivo exposure level and stability of Tac, besides, this effect is better than Wuzhi capsule in same dose.